The symbolic game in the elaboration of mourning for the child of early childhood education - Disner, Gabriela da Silva; Carvalho, Luciana Ramos Rodrigues de; Moraes , Marcela Cristina de (Seven Editora, 2023)
Early childhood education, an essential stage for human development, enables the establishment of socio-affective relationships and bonds beyond the family environment, favoring the construction of the notion of individual and social identity, a process in which the child must be respected as a person in formation in its integrality. However, the character of the inseparability of aspects of human development has only been considered in recent decades in the educational process and by the guiding documents of Brazilian education. The BNCC, in addition to reaffirming the link between educating and caring, arranged among the general competencies to be developed throughout basic education, the socio-emotional ones. Jean Piaget (1896-1980) in his broad trajectory of studies about child development, researched how the child constructs reality, considering the social, cognitive, physical, and affective aspects. In a constant process of assimilation and accommodation to the world, the child experiences unbalanced situations and can use the symbolic game as a means of compensating and/or settling conflicts, including dealing with one of the most challenging experiences that human beings can experience, the death of a loved one. In this article, we will present a case report addressing a situation of affective loss experienced by a 5-year-old child in the context of early childhood education, and how she re-elaborated and expressed her feelings through symbolic play. The theme has great relevance, especially in the pandemic context, in which educators have been challenged to welcome and assist students in the elaboration of their emotions and feelings. DOI:https://doi.org/10.56238/alookdevelopv1-065